Changing Inequality - Blank, Rebecca M. (Book collections on Project MUSE., 2011)
"Rebecca M. Blank offers the first comprehensive analysis of an economic trend that has been reshaping the United States over the past three decades: rapidly rising income inequality. In clear language, she provides an overview of how and why the level and distribution of income and wealth has changed since 1979, sets this situation within its historical context, and investigates the forces that are driving it. Among other factors, Blank looks closely at changes within families, including women's increasing participation in the work force. The book includes some surprising findings-for example, that per-person income has risen sharply among almost all social groups, even as income has become more unequally distributed. Looking toward the future, Blank suggests that while rising inequality will likely be with us for many decades to come, it is not an inevitable outcome. Her book considers what can be done to address this trend, and also explores the question: why should we be concerned about this phenomenon?"--Provided by publisher.